Tính bằng cách thuận tiện nhất:
78,43 - 52,28 - 7,65
________________________________________________________________________________________________________________________
45,67 x 45 + 59 x 45,67 - 45,67 x 4
______________________________________________________________________________________________
78,43-52,28-7,65
=78,43-(52,28+7,65)
=78,43-59,93
=18,5
\(45,67\times45+59\times45,67-45,67\times4\)
\(=45,67\times\left(45+59-4\right)\)
\(=45,67\times100=4567\)
78,43 - 52,28 - 7,65
= (78,43 - 52,28) - 7,65
= 26,15 - 7,65
= 14,5
45,67 x 45 + 59 x 45,67 - 45,67 x 4
= 45,67 x ( 45 + 59 - 4)
= 45,67 x 100
= 4567